Urgensi Pembelajaran Berbasis Teknologi Dalam Meningkatkan Kinerja Guru di Sekolah Menengah Pertama Negeri 2 Sarolangun - Wasnadi Wasnadi; Rusmini Rusmini; Shalahudin Shalahudin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze​​​​​ level​​​​ k e ready a n d a nk o mpet e nsi Teacher in carrying out educational learning​​​​​​​ Technology-based Islamic learning at SMAN 2 Sarilanggun . The results of this study indicate that technology - based learning planning has been implemented well by Islamic Religious teachers because educators have prepared a Learning Implementation Plan, have selected digital media and have prepared digital teaching materials . Technology-based Islamic Religious Education (ISE) learning has been successful, as it facilitates learning through the use of digital media. Another indicator is that ISE teachers have linked their learning to current phenomena, with satisfactory results. The implementation of technology-based evaluation of Islamic Religious Education learning has been successful. Educators conducted learning evaluations using technologies such as Google Forms and Quizizz. The principal worked with the school to improve teacher performance. learning​​​​​​ education​​​​​​ I slam b e rb a sis technology that can​​​​ applied kan ns e ca ra​​​​​​ Effective and efficient . The principal of SMPN 2 Sarolangun 's efforts to improve teacher performance by carrying out management functions in full , such as planning by holding work program meetings, assigning tasks according to skills, planning digital learning training, and implementing routine and continuous coaching.